Sustainable Digital Landscapes of Experience: The Unesco Memory of the World Programme - Calise, Anna; Raffa, Maria (Aisthesis, 2025)
The aim of this paper is to address the importance of sustainability standards in the creation of heritage digital landscapes, which are essential to ensure the longevity and meaningful impact of cultural heritage in the digital era. The present research stresses how the concept of sustainability should be addressed in its multifaceted nature, accounting not only for ecological but also social, economic and cultural perspectives, and that it should be taken into consideration in all the phases of digitization, ensuring a comprehensively sustainable process. In order to shed light on these issues, this paper introduces the current state of the art of the matter; examines the challenges of digitizing cultural heritage; argues for a broader perspective on sustainability and presents the case study of the UNESCO Memory of the World Programme to evaluate the sustainability of digitization efforts within the creation of an international and cross cultural experiential field.